The Effect of Profitability on Cash Dividends in Consumer Goods Industry Sector Companies on the Indonesian Stock Exchange (Period 2015-2019) - Hia, Epifania (Interconnection: An Economic Perspective Horizon, 2023)
The purpose of this study was to determine the effect of profitability by using the Return on Equity (ROE) variable on cash dividends. This study examines the independent variable, namely profitability taken from ROE (Return on equity), and the dependent variable, namely Cash Dividend. This research was conducted on companies in the Consumer Goods Industry sector listed on the IDX for the 2015-2019 period. The study was conducted on 53 companies in the Consumer Goods Industry sector and there were only 5 companies that met the sampling criteria. The research data is secondary data in the form of financial statements of 5 companies in the Consumer Goods Industry sector published on the IDX. The study analyzed the relationship between financial performance with the variable Return on Equity (ROE) and Cash Dividend. The statistical method used is simple linear regression by testing the classical assumptions first. Partial test results (t-test) obtained Return on Equity (ROE) known t-count (6.235) < t-table (2.0687) and Sig. (0.00) <0.05, which means that the Return on Equity (ROE) variable has a significant effect on cash dividends for Consumer Goods Industry Companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The results of the simple linear regression test are Y = 50,194 + 4.875X1 + e, it is known that the value of constant (a) is 50,194 and the value of the ROE variable is (4.875) where every one unit increase in ROE will increase the value of cash dividends by 4.875. The results of the R Square test show that the R Square value is 0.628 or 62.8%, which means that the ROE variable only affects cash dividends of 62.8%. The rest of 37.2% is influenced by other variables that are not included in the study.